Eccrine Porocarcinoma of the face is a great imitator with aggressive behavior - Konstantinos Seretis; Nikolaos Bounas; Evangeli Lampri; Efstathios Lykoudis (Mattioli1885, 2022)
Introduction: Eccrine porocarcinoma (EPC) is a rare subtype of non-melanoma skin cancer developing in the intraepithelial portion of eccrine sweat glands. It is branded with a highly metastatic potential and increased rate of local recurrence after treatment. EPC showcased a trend of developing on the extremities, with presentation on the face sparse. Objectives: Aim of the study was to evaluate the frequency, clinical features, and course of this malignancy presented on the face. Methods: A retrospective review of the skin cancers excised between January 2010 and June 2021 was conducted in the plastic surgery department of a tertiary hospital. Patients were included in the study if EPC on the face was histologically confirmed. A prospectively maintained clinic database and the pathological reports were used to collect data. Results: 4 EPC cases on the face out of 3984 confirmed skin cancers were identified. None of the cases was suspected clinically, but the diagnosis was established following the histopathologic examination. An aggressive postoperative behavior was confirmed in two cases. Conclusions: The variance in the clinical presentation and the non-specific characteristics are perplexing clinical diagnosis, with the histopathologic examination representing the current standard for confirmation. Early diagnosis and adequate surgical resection are recommended as treatment cornerstones. Clinical awareness ought to be raised and a definitive treatment protocol be established for optimized results.